2020
DOI: 10.1016/j.applanim.2020.104965
|View full text |Cite
|
Sign up to set email alerts
|

Broadcasting human voice to piglets (Sus scrofa domestica) modifies their behavioural reaction to human presence in the home pen and in arena tests

Abstract: Broadcasting human voice to piglets (Sus Scrofa domestica) modifies their behavioural reaction to human presence in the home pen and in arena tests, Applied Animal Behaviour Science (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
(75 reference statements)
1
11
0
Order By: Relevance
“…In addition to the behaviors previously mentioned, the greater latencies to approach and to contact the stockperson, the longer time they spent away from the stockperson and the increased avoidance of physical contact (e.g., greater locomotor activity when the stockperson tried to stroke them and less accepted strokes) suggests that control pigs were not just fearful of a new environment but of the human as well [ 55 ]. These results are in line with previous studies that have shown that pigs receiving a minimal amount of human contact, limited to routine husbandry, are highly fearful of humans compared to pigs exposed to a regular positive contact [ 8 , 11 ] or to daily human presence inside the pen [ 8 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to the behaviors previously mentioned, the greater latencies to approach and to contact the stockperson, the longer time they spent away from the stockperson and the increased avoidance of physical contact (e.g., greater locomotor activity when the stockperson tried to stroke them and less accepted strokes) suggests that control pigs were not just fearful of a new environment but of the human as well [ 55 ]. These results are in line with previous studies that have shown that pigs receiving a minimal amount of human contact, limited to routine husbandry, are highly fearful of humans compared to pigs exposed to a regular positive contact [ 8 , 11 ] or to daily human presence inside the pen [ 8 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, most of the behaviors displayed by the control animals were likely triggered primarily by fear. Unlike the observer pigs, the control pigs were distressed, as indicated by the increase in time spent looking at the stockperson [ 11 , 52 ], the increased amount of low-pitched [ 46 ] and high-pitched vocalizations emitted [ 53 , 54 ], and the occurrence of eliminative behaviors (defecation and urination) during the interaction with the stockperson [ 55 ]. All of these behaviors have been observed in pigs exposed to stressful and negative situations [ 56 ], such as introduction to a novel environment [ 57 ], isolation from conspecifics [ 53 , 57 , 58 ] and confrontation with a human in a human-approach test [ 11 , 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to better describe what are the most efficient human signals and behaviors that promote positive emotional states using a multimodal approach: voice? ( 45 ), shape? facial expression?…”
Section: Discussionmentioning
confidence: 99%
“…As tamed piglets received positive contacts everytime they were in the presence of the human, they may have expected contacts when approaching her and experienced an absence of reward during the test. This has already been hypothetised in piglets deprived from human voice during interactions after a period of habituation to it (Bensoussan et al 2020). Untamed piglet on the contrary never experienced additional positive contacts and being close to the human, having the possibility to investigate her may be some kind of reward after the period of total isolation.…”
Section: Discussionmentioning
confidence: 92%
“…Pigs may recognise a human providing positive contacts compared to an unfamiliar one and adapt their behaviour accordingly (Brajon et al, 2015c). Pigs may be sensitive to human voice and respond accordingly (Bensoussan et al, 2019(Bensoussan et al, , 2020. Pigs vocalisations are diverse and linked to their emotional states, attested by the use of positive or negative call types (Briefer et al, 2019(Briefer et al, , 2022 Manuscript -Preprint v3 -Grunt structure and human-pig relationship Tallet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%